Epidermal growth factor receptor metabolism and protein kinase activity in human A431 cells infected with Snyder-Theilen feline sarcoma virus or harvey or Kirsten murine sarcoma virus. - Cooper, J A (1983)
When human A431 cells, which carry high numbers of epidermal growth factor (EGF) receptors, are exposed to EGF, the total content of phosphotyrosine in cell protein is increased, the EGF receptor becomes phosphorylated at tyrosine, and new phosphotyrosine-containing 36,000- and 81,000-dalton proteins are detected. We examined the properties of A431 cells infected with Snyder-Theilen feline sarcoma virus, whose transforming protein has associated tyrosine protein kinase activity, and Harvey and Kirsten sarcoma viruses, whose transforming proteins do not. In all cases, the infected cells were more rounded and more capable of anchorage-independent growth than the uninfected cells. EGF receptors were assayed functionally by measuring EGF binding and structurally by metabolic labeling and immunoprecipitation. In no case did infection appear to alter the rate of EGF receptor synthesis, but infection reduced EGF receptor stability by about 50% for cloned Harvey sarcoma virus-infected cells and by 80% for cloned feline sarcoma virus-infected cells. The corresponding reductions in EGF binding were 70 and 90%, respectively. The proteins of feline sarcoma virus-infected A431 cells contained an increased amount of phosphotyrosine, and the 36,000- and 81,000-dalton phosphoproteins were detected. The EGF receptor was not detectably phosphorylated at tyrosine, however, unless the cells were exposed to EGF. The Harvey and Kirsten sarcoma virus-infected cells did not exhibit elevated levels of phosphotyrosine either in the total cell proteins or in the EGF receptor, nor were the 36,000- and 81,000-dalton proteins detectable. However, these phosphoproteins were found in the infected cells after EGF treatment. Thus, all of the infected A431 cells exhibited reduced EGF binding and increased degradation of EGF receptors, yet their patterns of protein phosphorylation were distinct from those of EGF-treated A431 cells.